EFL Students Ability in Differentiating English Homophone - Fermadi, Bayu; Kurniawan, Ildi; Lubis, Azhar Aziz (Journal of English Education and Teaching, 2024)
Homophones are when one or two written forms share the same pronunciation. Homophones often cause difficulties for students, especially for EFL students in listening skills because these words can be mistaken by students in listening because the word had same pronunciation. From this phenomenon, this study wanted to see the ability of students to differentiate homophones. This research design is descriptive research. In this research the population is the fifth-semester student of English education Department the researchers choose this population because this population had passed the listening class. The sample in this research used Cluster Sampling. There are 30 students selected as the sample of the research. The data was taken from a listening test with 30 items of question. Based on the analysis of the students’ results it is found that the overall score of the students was quite diverse. The test results indicated that students' ability to Differentiate homophones test was very good. This can be seen from the result from the test and overall score from most students got a very good predicate from the results of classifying scores using a score interval. From the findings above researchers had concluded that student’s ability in differentiating English homophone is very good.